Copolymer, dispersant, and resin composition

JP7608329B2Active Publication Date: 2025-01-06DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021513648
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-11
Filing Date
2020-04-07
Publication Date
2025-01-06
Estimated Expiration
2040-04-07

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、高温の状態で長時間保持した場合であっても、分散性を維持することのできる共重合体、並びに、該共重合体を含む分散剤及び樹脂組成物等、さらには該樹脂組成物等を用いた熱伝導性グリース及び該熱伝導性グリースを用いた放熱部材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608329000005
    Figure 0007608329000005
  • Figure 0007608329000006
    Figure 0007608329000006
  • Figure 0007608329000007
    Figure 0007608329000007
Patent Text Reader

Abstract

This copolymer has a (meth)acrylic monomer unit A having an anionic group, a (meth)acrylic monomer unit B having a cationic group, and a (meth)acrylic monomer unit C which is neither the (meth)acrylic monomer unit A nor the (meth)acrylic monomer unit B.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolymer, a dispersant, and a resin composition. [Background technology]

[0002] In recent years, electric vehicles and other electrically powered vehicles have become more widespread. Circuit boards used in the onboard power supply systems of electrically powered vehicles generally generate a large amount of heat due to the large voltage and current. This increased heat generation can cause circuit malfunctions and breakdowns. In addition, the battery packs that supply power to the electric motors of electrically powered vehicles generate heat through repeated charging and discharging. Continuing to use the battery pack at a high temperature can cause a decrease in its performance and lifespan.

[0003] Furthermore, such heat-related problems are not limited to electric vehicles, but also occur in electronic devices. As electronic devices become more compact and more sophisticated, the heat density inside them increases year by year, and the issue of how to efficiently dissipate the heat generated during use has become an issue.

[0004] Although the details of the cooling mechanism differ depending on the heat generating part, the heat is basically removed by contacting the heat generating part with a cooling member. In this case, if there is a gap between the heat generating part and the cooling member, the heat removal efficiency decreases, so in general, the heat is removed by indirectly contacting the heat generating part with the cooling member via a heat dissipation member.

[0005] Such heat dissipation members generally contain inorganic fillers in a resin that have been surface-treated with a silane coupling agent, etc. As a surface treatment agent other than the silane coupling agent, for example, a copolymer containing a polybutadiene structural unit, a structural unit having a hydrolyzable silyl group, and a structural unit having a polysiloxane skeleton is known (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-062552 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, it has been found that when a heat dissipating member using a conventional surface treatment agent or dispersant is kept at high temperature for a long time, dispersion destruction occurs, and the inorganic filler re-aggregates. When the inorganic filler in the heat dissipating member re-aggregates, the hardness of the heat dissipating member increases, and cracks may occur. In addition, such damage to the heat dissipating member also leads to a decrease in the reliability of electric vehicles, etc.

[0008] The present invention has been made in consideration of the above problems, and aims to provide a copolymer that can maintain its dispersibility even when held at high temperatures for a long period of time, as well as a dispersant and a resin composition containing the copolymer, and further a thermally conductive grease using the resin composition and a heat dissipation component using the thermally conductive grease. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that a (meth)acrylic copolymer having a specific structural unit can solve the above problems, thereby completing the present invention.

[0010] That is, the present invention is as follows. [1] A (meth)acrylic monomer unit A having an anionic group; A (meth)acrylic monomer unit B having a cationic group; a (meth)acrylic monomer unit C other than the (meth)acrylic monomer unit A and the (meth)acrylic monomer unit B; A copolymer having the formula: [2] The copolymer according to [1], wherein the anionic group includes at least one selected from the group consisting of a carboxy group, a phosphate group, and a phenolic hydroxy group. [3] The copolymer according to [1] or [2], wherein the (meth)acrylic monomer unit A further has an electron-withdrawing group bonded to the anionic group. [4] The copolymer according to any one of [1] to [3], wherein the cationic group includes at least one selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt. [5] The copolymer according to any one of [1] to [4], wherein the (meth)acrylic monomer unit B further has an electron-donating group bonded to the cationic group. [6] The copolymer according to any one of [1] to [5], wherein the (meth)acrylic monomer unit C includes at least one selected from the group consisting of an oxyalkylene skeleton, a siloxane skeleton, a hydrocarbon skeleton, and a phosphate diester skeleton. [7] 7. The copolymer according to claim 1, having a weight average molecular weight of 5,000 to 500,000. [8] The copolymer according to any one of [1] to [7], wherein a total content of the (meth)acrylic monomer units A and the (meth)acrylic monomer units B is 0.05 to 90 mol % relative to 100 mol % in total of the (meth)acrylic monomer units A, the (meth)acrylic monomer units B, and the (meth)acrylic monomer units C. [9] The copolymer according to any one of [1] to [8], wherein the content of the (meth)acrylic monomer unit A is 0.03 to 70 mol % relative to 100 mol % in total of the (meth)acrylic monomer unit A, the (meth)acrylic monomer unit B, and the (meth)acrylic monomer unit C.

[10] The copolymer according to any one of [1] to [9], wherein the content of the (meth)acrylic monomer unit B is 0.02 to 20 mol % relative to 100 mol % in total of the (meth)acrylic monomer unit A, the (meth)acrylic monomer unit B, and the (meth)acrylic monomer unit C.

[11] The copolymer according to any one of [1] to

[10] , wherein the content of the (meth)acrylic monomer unit C is 10 to 99.8 mol % relative to 100 mol % in total of the (meth)acrylic monomer unit A, the (meth)acrylic monomer unit B, and the (meth)acrylic monomer unit C.

[12] The copolymer according to any one of [1] to

[11] , wherein a molar ratio of the (meth)acrylic monomer unit A to the (meth)acrylic monomer unit B is 0.9 to 30.

[13] A dispersant comprising the copolymer according to any one of [1] to

[12] .

[14] A surface treatment agent comprising the copolymer according to any one of [1] to

[12] .

[15] A dispersion comprising the copolymer according to any one of [1] to

[12] and an inorganic filler.

[16] A resin composition comprising a resin, the copolymer according to any one of [1] to

[12] , and an inorganic filler.

[17] The resin composition according to

[16] , wherein the inorganic filler has electrical conductivity and / or thermal conductivity.

[18] The resin composition according to

[16] or

[17] , wherein the inorganic filler is at least one selected from the group consisting of boron nitride powder, aluminum nitride powder, aluminum oxide powder, silicon nitride powder, silicon oxide powder, magnesium oxide powder, metallic aluminum powder, and zinc oxide powder.

[19] The resin composition according to any one of

[16] to

[18] , wherein the resin comprises one or more resins selected from the group consisting of silicone-based resins, acrylic-based resins, and epoxy-based resins.

[20] A thermally conductive grease comprising the resin composition according to any one of

[16] to

[19] . 〔twenty one〕

[20] A heat conductive grease according to the present invention, an electronic component, and a heat sink, A heat dissipation member, in which the electronic component and the heat sink are bonded together via the thermally conductive grease. Effect of the Invention

[0011] According to the present invention, it is possible to provide a copolymer capable of maintaining dispersibility even when kept at high temperatures for a long period of time, as well as a dispersant and a resin composition containing the copolymer, and further a thermally conductive grease using the resin composition and a heat dissipation component using the thermally conductive grease. [Brief description of the drawings]

[0012] [Figure 1] 1 is a photograph showing a test piece after a crack resistance evaluation test in Comparative Example 3. [Diagram 2] 2 is a binarized image of the photograph of the test piece in FIG. 1. [Diagram 3] 13 is a photograph showing the test results of the amount of all-bleed in the bleed-out resistance test of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited thereto, and various modifications are possible within the scope of the gist of the present invention. Note that the (meth)acrylic monomer unit of the present invention means both a methacrylic acid monomer unit and an acrylic monomer unit.

[0014] [Copolymer] The copolymer of the present embodiment has (meth)acrylic monomer units A having an anionic group, (meth)acrylic monomer units B having a cationic group, and (meth)acrylic monomer units C other than the (meth)acrylic monomer units A and the (meth)acrylic monomer units B. The copolymer of the present embodiment has the above-mentioned structure, and thus can maintain dispersibility even when kept at high temperature for a long period of time. The reason for this is considered to be as follows, but is not limited thereto.

[0015] At the interface where two different substances come into contact, such as the surface of a dispersoid dispersed in a dispersion medium, a certain potential difference occurs, attracting counterions and forming an electric double layer consisting of a stationary phase and a diffuse double layer. The spread of counterions on the surface of the dispersoid is also called the thickness of the electric double layer. When the dispersoids approach each other, the counterions overlap and the repulsive force increases. The copolymer of this embodiment is considered to have the effect of increasing the thickness of this electric double layer by having both anionic and cationic groups in the molecule. More specifically, one of the anionic group and cationic group of the copolymer is arranged near the surface of the dispersoid as a counterion. The other group (secondary ion) that does not function as a counterion is arranged farther away from the surface of the dispersoid, and a secondary ion layer can be further formed there. In this way, the thickness of the electric double layer on the surface of the inorganic filler is increased, and it is considered that the electrostatic repulsive force can be applied farther away from the surface of the dispersoid where the van der Waals force acts, and the dispersibility of the dispersoid can be well maintained even when it is held at a high temperature for a long time.

[0016] In this embodiment, the term "monomer" refers to a monomer having a polymerizable unsaturated bond before polymerization, and the term "monomer unit" refers to a repeating unit that constitutes a part of a copolymer after polymerization and is derived from a specific monomer. In the following description, "(meth)acrylic monomer unit A" and the like are also simply referred to as "unit A".

[0017] ((Meth)acrylic monomer unit A having an anionic group) The (meth)acrylic monomer unit A is a repeating unit having an anionic group. The anionic group is not particularly limited, but may be, for example, a carboxy group, a phosphoric acid group, a phenolic hydroxy group, or a sulfonic acid group. Among these, it is preferable that the anionic group is at least one selected from the group consisting of a carboxy group, a phosphoric acid group, and a phenolic hydroxy group. By having such a group, the dispersibility of the dispersoid tends to be further improved.

[0018] In addition, it is preferable that the unit A further has an electron-withdrawing group bonded to the anionic group. Such an electron-withdrawing group is not particularly limited as long as it has the effect of stabilizing the anion of the anionic group. For example, an acrylic monomer containing an electron-withdrawing substituent such as a halogen element on the carbon atom at the α-position of the carboxyl group may be used. By having such a group, the dispersibility of the dispersoid tends to be further improved.

[0019] It is preferable that the unit A does not have an electron-donating group bonded to the anionic group or has a group with low electron-donating ability. Such an electron-donating group is not particularly limited as long as it has the effect of destabilizing the anion of the anionic group. For example, an acrylic monomer that does not contain a substituent of an electron-donating group such as a methyl group on the carbon atom at the α-position of the carboxyl group may be used. By adopting such a structure, the dispersibility of the dispersoid tends to be further improved.

[0020] Such (meth)acrylic monomers are not particularly limited, but examples thereof include acrylic acid, methacrylic acid, acid phosphooxypropyl methacrylate, acid phosphooxy polyoxyethylene glycol monomethacrylate, acid phosphooxy polyoxypropylene glycol monomethacrylate, phosphoric acid modified epoxy acrylate, 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, 4-hydroxyphenyl acrylate, 4-hydroxyphenyl methacrylate, 2-methacryloyloxyethyl succinic acid, 2-acrylamido-2-methylpropanesulfonic acid, etc. Among these, acrylic acid, 2-methacryloyloxyethyl phosphate, 4-hydroxyphenyl methacrylate, and 2-acrylamido-2-methylpropanesulfonic acid are preferred, and acrylic acid is more preferred. By including units derived from such monomers, the affinity to dispersoids is improved, and the dispersibility of dispersoids tends to be improved. The unit A may be used alone or in combination of two or more kinds.

[0021] ((Meth)acrylic Monomer Unit B Having a Cationic Group) The (meth)acrylic monomer unit B is a repeating unit having a cationic group. The cationic group is not particularly limited, but for example, the cationic group is preferably one or more selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt. Among these, a tertiary amino group is more preferable. By having such a group, the dispersibility of the dispersoid tends to be further improved.

[0022] In addition, the unit B preferably further has an electron-donating group bonded to the cationic group. Such an electron-donating group is not particularly limited as long as it has the effect of stabilizing the cation of the cationic group. For example, an acrylic monomer containing an electron-donating substituent such as a methyl group on the carbon atom at the α-position of the amino group may be used. By having such a group, the dispersibility of the dispersoid tends to be further improved.

[0023] It is preferable that the unit B does not have an electron-withdrawing group bonded to a cationic group or has a group with low electron-withdrawing ability. Such an electron-withdrawing group is not particularly limited as long as it has the effect of destabilizing the cation of the cationic group. For example, an acrylic monomer that does not contain a substituent of an electron-withdrawing group such as a carboxyl group on the carbon atom at the α-position of the amino group may be used. By adopting such a structure, the dispersibility of the dispersoid tends to be further improved.

[0024] Such (meth)acrylic monomers are not particularly limited, but examples thereof include 1-aminoethyl acrylate, 1-aminopropyl acrylate, 1-aminoethyl methacrylate, 1-aminopropyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, t-butylaminoethyl (meth)acrylate, dimethylaminoethyl methacrylate quaternary salt, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, dimethylaminoethyl acrylate benzyl chloride quaternary salt, etc. Among these, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate and 2,2,6,6-tetramethyl-4-piperidyl methacrylate are preferred, and 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate is more preferred. By containing a unit derived from such a monomer, the affinity for the dispersoid is improved, and the dispersibility of the dispersoid tends to be improved. The unit B may be used alone or in combination of two or more kinds.

[0025] ((Meth)acrylic monomer unit C) The (meth)acrylic monomer unit C is a (meth)acrylic monomer unit other than the unit A and the unit B, and is a (meth)acrylic monomer that does not contain a cationic group or an anionic group in the molecule.

[0026] In the case where the copolymer of the present embodiment is mixed into a resin composition containing a thermoplastic resin or a thermosetting resin, it is preferable that the (meth)acrylic monomer C has a skeleton having high affinity or compatibility with the resin used in the resin composition. Such skeletons are not particularly limited, but examples thereof include amphiphilic skeletons such as oxyalkylene skeletons, siloxane skeletons such as dimethylsiloxane, hydrophobic skeletons such as alkyl and aryl hydrocarbon skeletons, and hydrophilic skeletons such as phosphoric acid diester skeletons. Among these, oxyalkylene skeletons, siloxane skeletons, and hydrocarbon skeletons are preferred, and siloxane skeletons and hydrocarbon skeletons are more preferred. By having such a skeleton, compatibility with the resin serving as the dispersion medium is further improved, and the dispersibility of the dispersoid in the resin composition tends to be further improved.

[0027] Such (meth)acrylic monomers are not particularly limited, and examples thereof include (meth)acrylic monomers having an oxyalkylene skeleton, such as ethoxycarbonylmethyl (meth)acrylate, phenol ethylene oxide modified (meth)acrylate, phenol (ethylene oxide 2 mol modified) (meth)acrylate, phenol (ethylene oxide 4 mol modified) (meth)acrylate, paracumylphenol ethylene oxide modified (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, nonylphenol (ethylene oxide 4 mol modified) (meth)acrylate, nonylphenol (ethylene oxide 8 mol modified) (meth)acrylate, nonylphenol (propylene oxide 2.5 mol modified) acrylate, 2-ethylhexylcarbitol (meth)acrylate, ethylene oxide modified phthalic acid (meth)acrylate, ethylene oxide modified succinic acid (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, (Meth)acrylic monomers in which the ester moiety has a hydrocarbon skeleton, such as meth)acrylate and methoxylated cyclodecatriene (meth)acrylate; (meth)acrylic monomers having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate;(Meth)acrylic monomers having an amide bond, such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, diacetone(meth)acrylamide, or acryloylmorpholine; (meth)acrylic monomers having a siloxane skeleton, such as α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane; (meth)acrylic monomers having a phosphoric acid diester skeleton, such as (meth)acryloyloxyethyl dialkyl phosphate; 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexa Examples of the polyfunctional (meth)acrylic monomer include diol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, 2-ethyl-2-butyl-propanediol (meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, 2-(1,2-cyclohexacarboximide)ethyl (meth)acrylate, hexanediol di(meth)acrylate, and polyfunctional (meth)acrylic monomers having a bisphenol structure. The unit C may be used alone or in combination of two or more types.;

[0028] The weight-average molecular weight of the (meth)acrylic monomer C is preferably 300 to 20,000, more preferably 1,000 to 15,000, and even more preferably 3,000 to 12,500. When the weight-average molecular weight of the (meth)acrylic monomer C is 300 or more, the affinity to the dispersion medium is improved, and the dispersibility of the dispersoid tends to be improved. In addition, when the weight-average molecular weight of the (meth)acrylic monomer C is 20,000 or less, the viscosity of the composition obtained when the copolymer is mixed with other resins and other components is reduced, and the handleability tends to be improved.

[0029] The total content of the units A and B is preferably 0.05 to 90 mol%, more preferably 0.2 to 70 mol%, relative to 100 mol% in total of the units A, B, and C. When the total content of the units A and B is 0.05 mol% or more, the affinity to the dispersion medium is improved, and the dispersibility of the dispersoid tends to be improved. In addition, when the total content of the units A and B is 90 mol% or less, the viscosity of the composition obtained when the copolymer is mixed with other resins and other components is reduced, and the handleability tends to be improved.

[0030] The content of unit A is preferably 0.03 to 70 mol%, more preferably 0.1 to 15 mol%, relative to 100 mol% in total of unit A, unit B, and unit C. When the content of unit A is 0.03 mol% or more, the affinity to the dispersion medium is improved, and the dispersibility of the dispersoid tends to be improved. In addition, when the content of unit A is 70 mol% or less, the viscosity of the composition obtained when the copolymer is mixed with other resins and other components is reduced, and the handleability tends to be improved.

[0031] The molar ratio of units A to units B is preferably 0.01 to 200, more preferably 0.9 to 30, and more preferably 1.0 to 10. When the molar ratio of units A to units B is within the above range, the affinity to the dispersion medium is further improved, and the dispersibility of the dispersoid tends to be further improved.

[0032] The content of the unit B is preferably 0.02 to 20 mol %, more preferably 0.1 to 5 mol %, relative to 100 mol % in total of the units A, B, and C. By making the content of the unit B 0.02 mol % or more, the affinity for the filler is improved. In addition, by making it 20 mol % or less, the handleability resulting from the viscosity of the copolymer is improved.

[0033] The content of unit C is preferably 10 to 99.8 mol %, more preferably 30 to 99 mol %, relative to 100 mol % in total of unit A, unit B, and unit C. By making the content of unit C 10 mol % or more, the handleability resulting from the viscosity of the copolymer becomes good. Also, by making it 99 mol % or less, the affinity for the filler becomes good.

[0034] The weight-average molecular weight of the copolymer is preferably 5,000 to 500,000, more preferably 7,000 to 100,000. By having the weight-average molecular weight of the copolymer be 5,000 or more, the dispersibility can be maintained even when the composition is kept at a high temperature for a long time, and the hardness of the composition can be suppressed from increasing. In addition, by having the weight-average molecular weight of the copolymer be 5,000 or more, the shape retention of the composition when blended with an inorganic filler or a resin is improved, and the resistance to slippage and dripping of the composition when applied to an inclined or vertical surface is improved. In addition, by having the weight-average molecular weight of the copolymer be 500,000 or less, the viscosity of the composition obtained when the copolymer is mixed with other resins or other components is further reduced, and the handleability tends to be further improved. The weight-average molecular weight can be determined by GPC (gel permeation chromatography).

[0035] [Method for producing copolymer] The method for producing the copolymer of the present embodiment is not particularly limited, and a known polymerization method for a (meth)acrylic monomer can be used. Examples of the polymerization method include radical polymerization and anionic polymerization. Among these, radical polymerization is preferred.

[0036] The thermal polymerization initiator used in the radical polymerization is not particularly limited, but may be, for example, an azo compound such as azobisisobutyronitrile; an organic peroxide such as benzoyl peroxide, tert-butyl hydroperoxide, or di-tert-butyl peroxide. The photopolymerization initiator used in the radical polymerization is not particularly limited, but may be, for example, a benzoin derivative. In addition, known polymerization initiators used in living radical polymerization such as ATRP or RAFT may also be used.

[0037] The polymerization conditions are not particularly limited, and can be appropriately adjusted depending on the initiator and boiling point of the solvent used, as well as the types of other monomers.

[0038] The order of addition of the monomers is not particularly limited. For example, from the viewpoint of synthesizing a random copolymer, the monomers may be mixed to initiate polymerization, or from the viewpoint of synthesizing a block copolymer, the monomers may be added sequentially to the polymerization system.

[0039] [Dispersant] The dispersant of the present embodiment contains the copolymer, and may contain a solvent or other optional additives as necessary. The copolymer may also be used alone as a dispersant and added to a mixture of dispersoid and dispersion medium.

[0040] A dispersant is used for the purpose of uniformly dispersing a dispersoid in a dispersion medium. This prevents aggregation and sedimentation of the dispersoid in a mixture of the dispersoid and the dispersion medium, improving stability, and also allows the dispersoid to be contained in a high concentration in the dispersion medium and reduces the viscosity of the mixture. In addition, various effects associated with improved dispersibility of the dispersoid can be improved.

[0041] The dispersant of the present embodiment disperses the dispersoid by electrostatic repulsion by the copolymer, and can prevent the dispersoid from re-aggregating with itself. The copolymer may also have a dispersibility improving effect by steric hindrance repulsion. The dispersoid is not particularly limited, but may be, for example, one contained in the resin composition described later.

[0042] [Surface treatment agent] The surface treatment agent of the present embodiment contains the copolymer and may contain a solvent or other optional additives as necessary. The copolymer may also be used alone as a surface treatment agent to be applied to the surface of an object.

[0043] Surface treatment agents are used for the purpose of modifying the surface properties of an object, thereby improving or modifying surface properties such as the affinity and adhesion between the object and other components, as well as smoothness, and forming a highly stable film on the surface of the object to protect it.

[0044] The surface treatment agent of the present embodiment can modify the affinity between the target and other components through the copolymer by treating the target surface with the copolymer. The target material of the surface treatment agent is not particularly limited, and can be, for example, a material contained in the resin composition described below. The size of the target of the surface treatment agent is not particularly limited, and can be a wide range of materials, from nano-order or micro-order particles to milli-order, centimeter-order, or meter-order materials.

[0045] [Dispersion] The dispersion of the present embodiment includes the copolymer and an inorganic filler, and may include a solvent or other optional additives as necessary. The dispersion of the present embodiment is a dispersion in which the inorganic filler, which is a dispersoid, is dispersed by the copolymer, and can be used, for example, as a raw material when preparing a resin composition described later. Examples of the inorganic filler include those exemplified in the resin composition described later.

[0046] [Resin composition] The resin composition of the present embodiment contains a resin, the copolymer, and an inorganic filler, and may contain a solvent and other optional additives as necessary. The resin composition of the present embodiment is a composition in which the inorganic filler, which is a dispersoid, is dispersed in the resin by the copolymer.

[0047] The content of the copolymer is preferably 0.1 to 5 mass% and more preferably 0.5 to 4 mass% based on the total amount of the inorganic filler. When the content of the copolymer is 0.5 mass% or more based on the total amount of the inorganic filler, the dispersibility of the inorganic filler tends to be improved. Also, when the content of the copolymer is 5 mass% or less based on the total amount of the inorganic filler, the thermal conductivity of the resin composition tends to be improved.

[0048] The inorganic filler is not particularly limited, and examples thereof include inorganic fillers having electrical conductivity and / or thermal conductivity. Examples of such inorganic fillers include one or more selected from boron nitride powder, aluminum nitride powder, aluminum oxide powder, silicon nitride powder, silicon oxide powder, magnesium oxide powder, metallic aluminum powder, and zinc oxide powder. Among these, aluminum oxide powder and aluminum nitride powder are preferred, and aluminum oxide powder is more preferred. By using such an inorganic filler, the electrical conductivity and / or thermal conductivity of the resin composition tends to be further improved. In addition, by using such an inorganic filler in combination with the above-mentioned polymer, it is possible to more highly fill the inorganic filler in the resin composition. This makes it possible to further improve the electrical conductivity and / or thermal conductivity that improves depending on the amount of inorganic filler filled.

[0049] The average particle size of the inorganic filler is preferably 0.4 to 120 μm, more preferably 5 to 80 μm. By making the average particle size of the inorganic filler 0.4 μm or more, the thermal conductivity and oil-bleeding resistance are improved. In addition, by making it 120 μm or less, the moldability of the composition filled with the inorganic filler is improved.

[0050] The inorganic filler may be a mixture of inorganic fillers having a plurality of average particle sizes. Compared with the case where only an inorganic filler having a single average particle size is contained, by using an inorganic filler having a smaller average particle size, the gaps between the large-diameter inorganic fillers can be filled with the small-diameter inorganic fillers. Therefore, by using a mixture of inorganic fillers having a plurality of average particle sizes, it is possible to more highly fill the inorganic filler in the resin composition. Usually, when the inorganic filler is highly filled in this way, the viscosity is significantly increased, and problems such as the inability to handle or the inability to uniformly disperse the inorganic filler may occur. In contrast, by using the copolymer, such problems associated with high filling can be suppressed. This makes it possible to further improve the electrical conductivity and / or thermal conductivity that improves depending on the amount of inorganic filler filled.

[0051] The content of the inorganic filler is preferably 80 to 95 mass%, more preferably 80 to 94 mass%, and even more preferably 88 to 93 mass% based on the total amount of the resin composition. When the content of the inorganic filler is 80 mass% or more, the electrical conductivity and / or thermal conductivity tends to be further improved. Also, when the content of the inorganic filler is 95 mass% or less, the dispersibility of the inorganic filler in the resin composition becomes good.

[0052] The resin is not particularly limited, and examples thereof include thermosetting resins such as silicone resin, epoxy resin, phenol resin, cyanate resin, melamine resin, urea resin, thermosetting polyimide, and unsaturated polyester resin; and thermoplastic resins such as acrylic resin, polyolefin resin, polycarbonate resin, polyester resin, vinyl chloride resin, urethane resin, polyamide resin, and ABS (acrylonitrile-butadiene-styrene) resin. Among these, it is preferable to use one or more resins selected from the group consisting of silicone resin, acrylic resin, and epoxy resin. When using a thermosetting silicone resin, for example, it can be used as a thermally conductive grease in a state in which the crosslinking reaction is advanced by heating at 25°C to 200°C for 0.5 hours to 24 hours in advance. In addition, an electronic component and a heat sink may be joined with the resin composition before curing, and then heated under the same conditions for use.

[0053] The optional additives are not particularly limited, but examples thereof include silane coupling agents, antioxidants, and metal corrosion inhibitors.

[0054] The resin composition of the present embodiment can be produced by kneading using a planetary mixer, a universal mixer, a kneader, a hybrid mixer, or the like.

[0055] [Thermal conductive grease] The thermally conductive grease of this embodiment contains the above-mentioned resin composition. In other words, the thermally conductive grease of this embodiment contains a resin, the above-mentioned copolymer, and an inorganic filler, and may contain a solvent or other optional additives as necessary. The thermally conductive grease of this embodiment is a dispersoid, that is, an inorganic filler, dispersed in a base oil by the copolymer.

[0056] The content of the copolymer and the type and content of the inorganic filler in the thermal conductive grease can be the same as those in the above resin composition. The thermal conductive grease of this embodiment also includes the resin composition in which the components in the resin composition are cured or semi-cured. For example, the resin composition in the state of being heated at 25°C to 200°C for 0.5 hours to 24 hours to advance the crosslinking reaction can be used as the thermal conductive grease.

[0057] [Heat dissipation member] The heat dissipation member of the present embodiment includes the above-mentioned thermally conductive grease, an electronic component, and a heat sink, and the electronic component and the heat sink are bonded together via the thermally conductive grease.

[0058] Here, the electronic components are not particularly limited, but examples thereof include heat-generating electronic components such as motors, battery packs, circuit boards used in on-board power supply systems, power transistors, microprocessors, etc. Among these, electronic components used in on-board power supply systems for vehicles are preferred. The heat sink is not particularly limited as long as it is a component configured for the purpose of dissipating or absorbing heat.

[0059] The method of bonding an electronic component and a heat sink via a thermally conductive grease is not particularly limited. For example, a heat dissipation member may be obtained by bonding an electronic component and a heat sink using a thermally conductive grease that has been heated and cured or semi-cured in advance, or a heat dissipation member may be obtained by bonding an electronic component and a heat sink using a thermally conductive grease and then heating the electronic component and the heat sink to bond them together. The heating conditions are not particularly limited, but may be, for example, conditions of 25°C to 200°C for 0.5 hours to 24 hours. EXAMPLES

[0060] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0061] <Monomers for preparing copolymers> The following raw materials were used in the polymerization of the copolymers in the examples. ((Meth)acrylic monomer A having an anionic group) (A-1) Acrylic acid, manufactured by Toagosei Co., Ltd. (A-2) 4-Hydroxyphenyl methacrylate, manufactured by Seiko Chemical Co., Ltd. (A-3) 2-Methacryloyloxyethyl acid phosphate, "Light Ester P-1M" manufactured by Kyoeisha Chemical Co., Ltd. (A-4) 2-acrylamido-2-methylpropanesulfonic acid, manufactured by Tokyo Chemical Industry Co., Ltd. ((Meth)acrylic monomer B having a cationic group) (B-1) 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, "ADEKA STAB LA-82" manufactured by ADEKA Corporation (B-2) 1-aminoethyl methacrylate, manufactured by Tokyo Chemical Industry Co., Ltd. ((Meth)acrylic monomer C) (C-1) Butyl acrylate, manufactured by Toagosei Co., Ltd. (C-2) α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane), JNC Corporation "Silaplane FM-0721" weight average molecular weight 5,000 (C-3) α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane), JNC Corporation "Silaplane FM-0711" weight average molecular weight 1,000 (C-4) α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane, JNC Corporation "Silaplane FM-0725" weight average molecular weight 10,000 (C-5) Methoxypolyethylene glycol methacrylate (the number of repeating polyethylene glycol units is 9), "M-90G" manufactured by Shin-Nakamura Kogyo Co., Ltd.

[0062] <Preparation of Copolymer> (Copolymer 1) The copolymer was prepared by the following method. First, 100 parts by mass of (meth)acrylic monomer consisting of 15 mol% acrylic acid, 0.1 mol% 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 84.9 mol% butyl acrylate was added to an autoclave equipped with a stirrer. Next, 0.05 parts by mass of azobisisobutyronitrile (manufactured by Tokyo Chemical Industry Co., Ltd.) was added as an initiator relative to 100 parts by mass of the total of (meth)acrylic monomers, and 1000 parts by mass of a mixed solution of toluene (special grade reagent) and 2-propanol (special grade reagent) in a volume ratio of 7:3 was added as a solvent, and the inside of the autoclave was replaced with nitrogen. Then, the autoclave was heated at 65°C in an oil bath for 20 hours to carry out radical polymerization. After the polymerization was completed, the mixture was degassed at 120°C under reduced pressure for 1 hour to obtain copolymer 1.

[0063] The polymerization rate was 98% or more when analyzed by gas chromatography based on 100% of the monomer charge, which suggested that the ratio of each monomer unit in the copolymer was approximately the same as the monomer charge ratio.

[0064] The weight average molecular weight of the obtained copolymer 1 was determined as a weight average molecular weight converted into standard polystyrene by using a GPC (gel permeation chromatography) method under the following measurement conditions. High-speed GPC equipment: Tosoh Corporation "HLC-8020" Columns: One Tosoh "TSK guardcolumn MP(xL)" 6.0mmID x 4.0cm, and two Tosoh "TSK-GELMULTIPOREHXL-M" 7.8mmID x 30.0cm (16,000 theoretical plates), for a total of three (total theoretical plates: 32,000) Developing solvent: Tetrahydrofuran Detector: RI (Differential Refractometer)

[0065] (Copolymer 2~18) Radical polymerization was carried out in the same manner as for copolymer 1, except that the monomers having the compositions shown in Tables 1 to 4 were used, to obtain copolymers 2 to 18. The polymerization rates of the obtained copolymers 2 to 18 were all 98% or more, and the ratios of the monomer units contained in the copolymers were estimated to be approximately the same as the monomer charge ratios. The weight average molecular weights were also determined in the same manner as above.

[0066] The monomer compositions shown in Tables 1 to 4 are shown as molar ratios (%). The molar ratios were calculated from the amounts and molecular weights of each monomer. The molar ratios of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane were calculated based on the weight average molecular weights of these monomers.

[0067] The compositions and weight average molecular weights of the copolymers 1 to 18 synthesized as above are shown in Tables 1 to 4 below.

[0068] <Preparation of resin (polybutyl acrylate)> Into an autoclave equipped with a stirrer, 100 parts by mass of butyl acrylate, 0.05 parts by mass of azobisisobutyronitrile as an initiator, and 1000 parts by mass of 2-propanol as a solvent were added, and the atmosphere in the autoclave was replaced with nitrogen. The autoclave was then heated in an oil bath at 75°C for 20 hours to carry out radical polymerization. After the polymerization was completed, the mixture was degassed under reduced pressure at 120°C for 1 hour to obtain polybutyl acrylate for resin preparation.

[0069] <Raw materials for resin composition preparation> (resin) Polybutyl acrylate Silicone oil: Shin-Etsu Silicone "KF-96-100cs" (Inorganic filler) Aluminum oxide, Denka Co., Ltd., "DAW45", average particle size 45 μm, Aluminum oxide, manufactured by Denka Co., Ltd., "DAW20", average particle size 20 μm, Aluminum oxide, Denka Co., Ltd., "DAW05", average particle size 5μm, Aluminum oxide, manufactured by Denka Co., Ltd., "ASFP40", average particle size 0.4 μm Boron nitride, manufactured by Denka Co., Ltd., "SGP", average particle size 18μm

[0070] The average particle size of the inorganic filler was measured using Shimadzu's "Laser Diffraction Particle Size Distribution Analyzer SALD-20." The evaluation sample was prepared by adding 50 ml of pure water and 5 g of the thermally conductive filler to be measured to a glass beaker, stirring with a spatula, and then dispersing for 10 minutes in an ultrasonic cleaner. The dispersion of the thermally conductive filler that had been dispersed was added drop by drop to the sampler part of the device using a dropper, and measurements were taken when the absorbance had stabilized. D50 (median diameter) was used as the average particle size.

[0071] <Preparation of Resin Composition> Example 1 53.5 parts by mass of aluminum oxide "DAW45", 4.5 parts by mass of "DAW20", 4.5 parts by mass of "DAW05", and 26.5 parts by mass of "ASFP40" were weighed, and 9.1 parts by mass of polybutyl acrylate and 1.9 parts by mass of copolymer 1 prepared previously were added to a universal mixer. Next, the mixture was vacuum heated and kneaded in a universal mixer at 150°C for 3 hours under conditions of an absolute pressure of 100 Pa or less to prepare a resin composition. The evaluation of the obtained resin composition is shown in Table 1.

[0072] (Examples 2 to 20 and Comparative Examples 1 to 6) Resin compositions were prepared in the same manner as in Example 1, except that the components shown in Tables 1 to 4 were used. The evaluations of the obtained resin compositions are shown in Tables 1 to 4. In addition, the resin compositions in Comparative Examples 3 to 6 use a silane coupling agent instead of the copolymer.

[0073] The physical properties of the resin composition were measured by the following methods.

[0074] [viscosity] Using a Thermo Scientific MARS III rotational rheometer, a 35 mmΦ parallel plate was used as the upper jig, and the resin composition was placed on a 35 mmΦ lower plate whose temperature could be controlled by a Peltier element. The resin composition was compressed to a thickness of 1 mm by the upper jig, and the protruding part was scraped off. Measurements were performed at 25°C. Shear rates were 1 to 10 s ー1 Measure the viscosity at a shear rate of 10 s ー1 The viscosity was used for evaluation.

[0075] When the viscosity is lower than 400 Pas, metal mask / screen printing and application by squeegee are possible, and workability is good. When the viscosity is between 400 Pas and 700 Pas, metal mask / screen printing and application by squeegee are not suitable, but it is suitable for dispensing from a syringe and application by an automatic applicator. When the viscosity is between 400 Pas and 1150 Pas, dispensing and application by an automatic applicator are possible, but it takes more time. When the viscosity is 1150 Pas or more, dispensing and application by an automatic applicator is difficult because it takes time, or dispensing and application by an automatic applicator is not possible.

[0076] [Crack resistance] Two 76 mm square non-alkali glass plates were prepared, and the resin composition was applied to the center of one of the glass plates to a diameter of 20 mm and a thickness of 1 mm, and the sample sandwiched between the other glass plate was kept in an environment of 150° C. and a heat resistance test was performed. After keeping for 24 hours, the presence or absence of cracks was visually confirmed.

[0077] FIG. 1 shows a photograph of the test piece after the crack resistance evaluation test of Comparative Example 3, and FIG. 2 shows an image obtained by binarizing the image data of the test piece after the crack resistance evaluation test of Comparative Example 3 using image processing software (GIMP2.0). In the binarized image, the black parts are voids caused by cracking of the resin composition, and the white parts are parts where the resin composition is present. Images thus binarized were created in each Example and Comparative Example, and the crack resistance rate was calculated based on these images. More specifically, the area ratio of the black parts was calculated from the total area, and this was taken as the crack rate. The evaluation criteria for crack resistance are shown below. A: Crack rate is 0% or more and less than 1% B: Crack rate 1% or more but less than 5% C: Crack rate 5% or more but less than 15% D: Crack rate 15% or more

[0078] [Bleed-out resistance] 0.65 g of the resin composition was applied in a roughly circular shape on a 76 mm square ground glass, left to stand in an oven at 150 ° C. for 24 hours, and then removed from the oven. Figure 3 shows a photograph showing the test results of the all-bleed amount of Comparative Example 3 after removal from the oven. As shown in Figure 3, it can be seen that the liquid component seeps out and forms a gray circle around the white resin composition in the center of the photograph. This type of liquid component is called seepage bleeding. The size of this circle was used as an index of the amount of bleeding, and the maximum distance from the end of the white resin composition to the end of the gray circle was evaluated as the amount of bleeding out.

[0079] [Thermal Conductivity] A rectangular copper jig with a heater embedded in it, with a tip of 100 mm 2 (10mm x 10mm) and a rectangular copper jig with a cooling fin attached, with a tip of 100mm 2 The resin composition was sandwiched between copper jigs (10 mm x 10 mm), and the thermal resistance was measured at gap thicknesses ranging from 0.05 mm to 0.30 mm. The thermal conductivity was calculated from the thermal resistance and thickness gradient and evaluated. The thermal resistance was evaluated by applying 10 W of power to the heater and holding it for 30 minutes, measuring the temperature difference (°C) between the copper jigs, Thermal resistance was calculated as follows: Thermal resistance (℃ / W) = {Temperature difference (℃) / Power (W)}. As for thermal conductivity, any thermally conductive grease with a thermal conductivity of 1 W / mK or more can be used without any problems for its intended use. The following indicators were used in the evaluation. Excellent: Thermal conductivity 2.0W / mK or higher Good: Thermal conductivity 1.0W / mK or more and less than 2.0W / mK Not acceptable: Thermal conductivity less than 1.0W / mK

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] [Table 4] [Industrial Applicability]

[0084] The copolymer of the present invention has industrial applicability as a dispersant or a surface treatment agent, or as a resin composition using the same.

Claims

1. A (meth)acrylic monomer unit A having an anionic group; a (meth)acrylic monomer unit B having a cationic group; and a (meth)acrylic monomer unit C other than the (meth)acrylic monomer unit A and the (meth)acrylic monomer unit B, The (meth)acrylic monomer unit C contains at least one selected from the group consisting of a siloxane skeleton and a phosphoric acid diester skeleton, With respect to a total of 100 mol % of the (meth)acrylic monomer unit A, the (meth)acrylic monomer unit B, and the (meth)acrylic monomer unit C, The content of the (meth)acrylic monomer unit A is 0.03 to 70 mol %, The content of the (meth)acrylic monomer unit B is 0.02 to 20 mol %, The content of the (meth)acrylic monomer unit C is 10 to 99.8 mol %, The weight average molecular weight is 5,000 to 500,000. Copolymer.

2. The copolymer according to claim 1 , wherein the anionic group comprises at least one selected from the group consisting of a carboxy group, a phosphate group, and a phenolic hydroxy group.

3. The copolymer according to claim 1 or 2, wherein the (meth)acrylic monomer unit A further has an electron-withdrawing group bonded to the anionic group.

4. The copolymer according to any one of claims 1 to 3, wherein the cationic group comprises at least one selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt.

5. The copolymer according to any one of claims 1 to 4, wherein the (meth)acrylic monomer unit B further has an electron donating group bonded to the cationic group.

6. The copolymer according to any one of claims 1 to 5, wherein the (meth)acrylic monomer unit C contains a siloxane skeleton.

7. The copolymer according to any one of claims 1 to 6, wherein a total content of the (meth)acrylic monomer unit A and the (meth)acrylic monomer unit B is 0.05 to 90 mol% relative to a total of 100 mol% of the (meth)acrylic monomer unit A, the (meth)acrylic monomer unit B, and the (meth)acrylic monomer unit C.

8. The copolymer according to any one of claims 1 to 7, wherein a molar ratio of the (meth)acrylic monomer unit A to the (meth)acrylic monomer unit B is 0.9 to 30.

9. A dispersant comprising the copolymer according to any one of claims 1 to 8.

10. A surface treatment agent comprising the copolymer according to any one of claims 1 to 8.

11. A dispersion comprising the copolymer according to any one of claims 1 to 8 and an inorganic filler.

12. A resin composition comprising a resin, the copolymer according to any one of claims 1 to 8, and an inorganic filler.

13. The resin composition according to claim 12 , wherein the inorganic filler has electrical conductivity and / or thermal conductivity.

14. The resin composition according to claim 12 or 13, wherein the inorganic filler is at least one selected from the group consisting of boron nitride powder, aluminum nitride powder, aluminum oxide powder, silicon nitride powder, silicon oxide powder, magnesium oxide powder, metallic aluminum powder, and zinc oxide powder.

15. The resin composition according to any one of claims 12 to 14, wherein the resin comprises one or more resins selected from the group consisting of silicone-based resins, acrylic-based resins, and epoxy-based resins.

16. A thermally conductive grease comprising the resin composition according to any one of claims 12 to 15.

17. A thermally conductive grease according to claim 16, an electronic component, and a heat sink, A heat dissipation member, in which the electronic component and the heat sink are bonded together via the thermally conductive grease.

Citation Information

Patent Citations

  • Tertiary amino group-containing high polymer compound, detergent composition, antifoulant composition and detergent antifoulant composition

    JP2002256030A

  • Detergent composition for mud-stain

    JP2005206833A

  • Polymer emulsifier and polyolefin-based resin emulsion using the same

    JP2009173752A

  • Water-soluble amphoteric copolymer, production method for the same, and application of the same

    JP2012251156A

  • Silica dispersion, and active energy ray-curable resin composition

    JP2016121350A